Sharing a Novel Experience of Treating Addiction to Opium and Derivatives with only Ayurvedic Approach- A Case Series - Anita Sharma,; Rinkesh Vishnoi,; Sunita Yadav,; Jyoti Rani, (International Journal of Ayurveda and Pharma Research, 2022)
Introduction: Opium and its derivative addiction are one of the most prevalent addictions in western Rajasthan, because it is easily available and is being used openly in social programs as the culture of the same. In western Rajasthan, mainly Doda poppy, opium milk, smack, tramadol, etc. are major forms of opium-derived addictions. Withdrawal symptoms such as nausea, vomiting, diarrhea, chills, body ache, sleeplessness and flu-like symptoms begin, these symptoms can grow severe enough to necessitate emergency medical attention, and in extreme situations, they might have life-threatening consequences for the user as a result of respiration depression, and pupil dilation in the later stages. The assessment was based on Clinical Opiate Withdrawal Scale (cows) before and after the treatment. Intervention: Efforts have been applied to depict 8 cases of opium addiction in form of series who have been treated with Ahiphenmochanadi vati in the dose of 250 mg twice a day and Sameergaja kerari rasa in the tapering method (Padanshika Krama) starting with the dose of 375 mg along with panchakarma procedures, Shirodhara with til tail, Abhayanga, and Swedana with Mahanarayan Tail and Dashmool kwath respectively for a period of 1 month. Reduction in cows scale was observed, about 75-80% of symptoms subsided in all cases and the results have been reported very encouraging within a period of twenty to thirty days. Conclusion: Altogether, multimodal Ayurveda treatment can be an effective and safe solution for smack addictions.